Mobile augmented reality game-based learning: teacher training using the EduPARK app - Pombo, Lúcia (2020)
With the mobile technology widespread, new functionalities are being integrated in devices, namely augmented reality (AR), which can be used to enhance learning. Combining mobile AR learning with game-based approaches supports new forms of instruction in the outdoors and students’ engagement and motivation for learning are enhanced. However, new practices require teacher training. This is the case of the EduPARK workshop that aims to support teachers in the development of innovative outdoor practices, using mobile devices, AR and games. In this exploratory case study, qualitative and quantitative data were collected from five editions of the EduPARK workshop through a mandatory questionnaire and a voluntary reflexive self-account. Results show that teachers value this training for: i) the access to new educational resources, ii) the practices changing support, iii) knowledge update, although not necessarily in what concerns mobile learning, AR and game-based approaches, and iv) learning about cross-subjects approaches to teaching.